(untitled) (Journal of Economic Research & Business Administration, 2015)
The problem of anticrisis management is multidimensional and requires (demands) deep consideration not only its(her) essence, consequences, but also sources of occurrence. The system of anticrisis management has arisen as a means of anticipation of a crisis condition of the economic subjects. In a basis of anticrisis management the not investigated approach of effective management in modern conditions of stable development of economy of the state lays new.